Nomination-Motivation Characteristics of Hemeronym of The Uzbek Language - Yuldashev Otabek Toshpulat ugli (Zien Journals, 2022)
The article describes some Uzbek language hemeronyms: nominative-motivational features of special names of press publications such as newspapers and magazines.
Keywords: Onomastic unit; appellative lexicon; hemeronym; press publications